Maximizing human development. (17th May 2013) - Engineer, Merwan; King, Ian
Abstract The Human Development Index (HDI) is widely used as a measure of well‐being. We examine the allocations implied by the maximization of this index using a standard growth model. Maximization leads to consumption (excluding education and health expenditures) being pushed to minimal levels. It also leads to the overaccumulation of education and/or health capital and possibly physical capital, relative to the standard golden rule. We propose an alternative specification for the HDI, where consumption replaces income as a proxy for decent standard of living. Maximization of this alternative implies a 'human development golden rule' which balances consumption, education and health expenditure. We advocate the method of optimization subject to constraints for revealing the policy implications of taking an achievement measure and its underlying philosophy seriously.